Spatially Ordered Arrays of Colloidal Inorganic Metal Halide Perovskite Nanocrystals via Controlled Droplet Evaporation in a Confined Geometry - Kwan Lee (MDPI AG, 2021)
Inorganic metal halide perovskite nanocrystals, such as quantum dots (QDs), have emerged as intriguing building blocks for miniaturized light-emitting and optoelectronic devices. Although conventional lithographic approaches and printing techniques allow for discrete patterning at the micro/nanoscale, it is still important to utilize intrinsic QDs with the concomitant retaining of physical and chemical stability during the fabrication process. Here, we report a simple strategy for the evaporative self-assembly to produce highly ordered structures of CsPbBr3 and CsPbI3 QDs on a substrate in a precisely controllable manner by using a capillary-bridged restrict geometry. Quantum confined CsPbBr3 and CsPbI3 nanocrystals, synthesized via a modified hot-injection method with excess halide ions condition, were readily adapted to prepare colloidal QD solutions. Subsequently, the spatially patterned arrays of the perovskite QD rings were crafted in a confirmed geometry with high fidelity by spontaneous solvent evaporation. These self-organized concentric rings were systemically characterized regarding the center-to-center distance, width, and height of the patterns. Our results not only facilitate a fundamental understanding of assembly in the perovskite QDs to enable the solution-printing process but also provide a simple route for offering promising practical applications in optoelectronics.